Smartphone in - app advertisements of higher education and its influences on purchase intention of students - Pham, Boi Hang (H. : ĐHQGHN, 2020)
The research aims to provide further understanding of smartphone in-app advertisements (SIA) and to explore how it can affect purchase intention of students in choosing higher education.